The roles of intra-household gendered dominance in unmet need for family planning across Myanmar - Phyu, Win Ei; Chamchan, Chalermpol (UI Scholars Hub, 2019)
Background: Unmet need for family planning in Myanmar (estimated 15.8% by the UN in 2017) is relatively high compared to other South East Asia countries. Moreover, Social Institutions and Gender Index in Myanmar is very high and cultural norms promote childbearing. Thus, this paper was conducted to examine role of intra-household gendered dominance (IHGD) in unmet need for family planning across Myanmar to set more effective intervention for family planning. Methods: The study utilized secondary data from 2015–2016 MDHS. Total 7,652 married women in reproductive age (MWRA) were included and 16% of them had unmet need for family planning. Binary Logistic Regression Analysis was conducted to examine the association of each explanatory variables with outcomes variables. Results: IHGD factors which are decision on women’s health and women’s attitude towards wife beating are significantly associated with unmet need. Moreover, socio-economic factors which are place of residence and women’s education level have significant impact on unmet need as well. Conclusion: Based on the findings of this study, the government of Myanmar should address dominance of social and cultural gender norms by conducting gender equality awareness campaign and family planning program should target to reach rural and uneducated women.